Combined continuous nanoparticle synthesis with chromatographic size classification - Gromotka, Lukas; Biegel, Markus; Damm, Cornelia; Traore, Nabi; Drobek, Dominik; Spiecker, Erdmann; Peukert, Wolfgang (Advanced Powder Technology, 2024)
In this paper, we report a combination of the continuous flow synthesis of gold nanoparticles (AuNPs) with subsequent purification and narrowing of the particle size distribution (PSD) by size-exclusion chromatography (SEC) by adapting the flow rates of synthesis and classification. First, we show scalability of chromatographic classification with respect to column dimension and the absence of irreversible nanoparticle adhesion on the column material. Two different syntheses lead to a large and widely distributed and a small and narrowly distributed AuNP dispersion, which are classified by a semipreparative column. The PSDs of individual fractions are characterized by analytical SEC. The broadly distributed AuNP dispersion was classified into three fractions with distinct PSDs. For the narrowly distributed AuNPs, the separation is almost independent of the mobile phase flow rate: coarse and fine fractions with almost identical PSDs and separation efficiency curves are observed irrespective of the flow rate. Even NP samples with narrow PSDs can be classified into multiple fractions with tailored PSDs while simultaneously removing dissolved impurities from the dispersion. With our study, we demonstrate the potential of a direct combination of continuous NP synthesis with chromatographic classification for the optimization of final PSDs and the simultaneous purification of nanoparticulate dispersions.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Continuous flow synthesis; Gold nanoparticles; Purification; Size classification; Size-exclusion chromatography

Efficient quenching sheds light on early stages of gold nanoparticle formation - Biegel, Markus; Schikarski, Tobias; Cardenas Lopez, Paola Ivonne; Gromotka, Lukas; Lübbert, Christian; Völkl, Andreas; Damm, Cornelia; Walter, Johannes; Peukert, Wolfgang (RSC Advances, 2023)
The formation mechanism of plasmonic gold nanoparticles (Au NPs) by fast NaBH4 induced reduction of the precursors is still under debate. In this work we introduce a simple method to access intermediate species of Au NPs by quenching the solid formation process at desired time periods. In this way, we take advantage of the covalent binding of glutathione on Au NPs to stop their growth. By applying a plethora of precise particle characterization techniques, we shed new light on the early stages of particle formation. The results of in situ UV/vis measurements, ex situ sedimentation coefficient analysis by analytical ultracentrifugation, size exclusion high performance liquid chromatography, electrospray ionization mass spectrometry supported by mobility classification and scanning transmission electron microscopy suggest an initial rapid formation of small non-plasmonic Au clusters with Au10 as the main species followed by their growth to plasmonic Au NPs by agglomeration. The fast reduction of gold salts by NaBH4 depends on mixing which is hard to control during the scale-up of batch processes. Thus, we transferred the Au NP synthesis to a continuous flow process with improved mixing. We observed that the mean volume particle sizes and the width of the particle size distribution decrease with increasing flow rate and thus higher energy input. Mixing- and reaction-controlled regimes are identified.
CRIS-Team Scopus Importer:2023-07-21